2015
DOI: 10.3892/ol.2015.3769
|View full text |Cite|
|
Sign up to set email alerts
|

β-hydroxyisovaleryl-shikonin induces human cervical cancer cell apoptosis via PI3K/AKT/mTOR signaling

Abstract: The present study aimed to investigate the inhibitory ability of β-hydroxyisovaleryl-shikonin (β-HIVS) on the proliferation of human cervical cancer HeLa cells and to identify the mechanism of this effect. The HeLa cells were treated with β-HIVS and the inhibition of cell growth was detected by an MTT assay. Flow cytometry was performed to analyze the apoptosis rate and cell cycle distribution of HeLa cells. Reverse transcription-polymerase chain reaction and western blot analysis were used to examine the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…31 Shikonin, one major bioactive component extracted from the roots of Lithospermum erythrorhizon, was found to be capable of inhibiting cervical cancer via inducing cell apoptosis and inhibiting cell proliferation. 14,15,32 Despite the inhibitory effect of shikonin in cell proliferation have been reported, the action of shikonin in EMT process in cervical cancer cells still remained unknown. Based on the results from the current study, we showed that shikonin inhibited cell proliferation, migration and invasion in both Hela and E-cadherin, down-regulation of vimentin and Snail).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Shikonin, one major bioactive component extracted from the roots of Lithospermum erythrorhizon, was found to be capable of inhibiting cervical cancer via inducing cell apoptosis and inhibiting cell proliferation. 14,15,32 Despite the inhibitory effect of shikonin in cell proliferation have been reported, the action of shikonin in EMT process in cervical cancer cells still remained unknown. Based on the results from the current study, we showed that shikonin inhibited cell proliferation, migration and invasion in both Hela and E-cadherin, down-regulation of vimentin and Snail).…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin inhibited triple-negative breast cancer (TNBC) cell metastasis by targeting the EMT via glycogen synthase kinase-3β (GSK-3β), a serine/threonine protein kinase, mediated suppression of β-catenin signaling, which highlighted the importance of shikonin as a potential candidate for novel anticancer therapeutics against TNBC. 13 Although the roles of shikonin in anti-cervical cancer were reported previously, [14][15][16] its precise molecular antitumor mechanism still remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin (SK) is an active ingredient isolated from the Chinese herb, Lithospermum erythrorhizon , which has been used for thousands of years in traditional Chinese medicine. It exerts anti-inflammatory [ 4 ], wound healing [ 5 ], and anti-cancer [ 6 , 7 ] effects. SK inhibits estrogen-dependent tumor cell growth and promotes the anti-estrogen effect of endocrine therapy in breast cancer [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the apoptosis of gastric smooth muscle cells has been shown to be important in the occurrence of diabetic gastroparesis (2,3), the mechanisms upstream of this process remain to be elucidated. The phosphoinositide-3-kinase (PI3K)-protein kinase B (AKT)-mammalian target of rapamycin (mTOR) pathway is an important intracellular signaling cascade capable of affecting a variety of cell behaviors, including cell proliferation, growth, apoptosis and metabolism (4,5). PI3K phosphorylates phosphatidylinositol 4,5-bisphosphate into phosphatidylinositol 3,4,5-triphosphate to recruit and activate AKT, which subsequently activates its downstream target molecule, mTOR.…”
Section: Introductionmentioning
confidence: 99%